PELATIHAN DAN PENDAMPINGAN PROGRAM PENGEMBANGAN DIRI DENGAN TEKNIK KETERAMPILAN DALAM BERKOMUNIKASI - Dharmanto, Agus; Astuti, Hani; Dewi, Nita Komala (Jurnal Terapan Abdimas, 2022)
Abstract. Self-development education activities in schools have begun to be included in the learning curriculum to explore and develop students' interests and talents so that they grow according to their abilities. Due to several problems experienced by Taman Harapan School, Bekasi, students are still unable to determine the interests, interests, desires that suit themselves, especially when going to college or the world of work. In connection with these problems, abdimas activities aim to help students to be able to develop themselves with skilled techniques in communication so that they can determine interests, interests, desires that suit themselves. The method is carried out by giving lectures, training, and mentoring students on how to develop self-potential and communication skills which was carried out for 3 (days) from 11 to 13 June 2022 at the Taman Harapan School Hall attended by 30 students. The results of this activity where participants' understanding increased and their communication skills also increased, as seen from the results of the pre-test and pors-test, namely 19%. The conclusion is that this training received good appreciation from the participants and the school and the obstacles faced were the lack of time where this training activity required intense time so that students could better understand their potential and communicate well. Abstrak. Kegiatan pendidikan pengembangan diri di sekolah sudah mulai masuk dalam kurikulum pembelajaran guna menggali dan mengembangkan minat dan bakat siswa agar tumbuh sesuai dengan bakat yang dimiliki. Dikarenakan adanya beberapa permasalahan yang dialami Sekolah Taman Harapan, Bekasi yakni siswa masih belum dapat menentukan ketertarikan, minat, keinginan yang sesuai dengan diri khususnya saat akan melanjutkan ke Perguruan Tinggi atau dunia kerja. Berkaitan dengan permasalahan tersebut maka kegiatan abdimas bertujuan membantu siswa untuk bisa mengembangkan dirinya dengan teknik terampil dalam berkomunikasi sehingga dapat menentukan ketertarikan, minat, keinginan yang sesuai dengan dirinya. Metode yang dilakukan dengan memberikan ceramah, pelatihan, dan pendampingan kepada siswa mengenai cara mengembangkan potensi diri dan keterampilan dalam berkomunikasi yang dilaksanakan selama 3 (hari) mulai dari tanggal 11 sampai 13 Juni 2022 di Aula Sekolah Taman Harapan dihadiri oleh 30 orang siswa. Hasil kegiatan ini dimana pemahaman peserta mengalami peningkatan dan kemampuan dalam berkomunikasi juga meningkat terlihat dari hasil pre-test dan pors-test yakni 19%. Kesimpulannya bahwa pelatihan ini mendapatkan apresiasi yang baik dari peserta maupun sekolah dan kendala yang dihadapi yakni waktu yang kurang dimana kegiatan pelatihan ini membutuhkan waktu yang intens agar siswa dapat lebih memahami mengenai potensi diri dan berkomunikasi yang baik.